2021
DOI: 10.1016/j.shaw.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Neck Pain and Associated Factors Among Sewing Machine Operators of Garment Factories in Mekelle City, Northern Part of Ethiopia, 2018, A Cross-Sectional Study

Abstract: Background Neck pain is a major public health problem among sewing machine operators working in textile factories. Even though the textile industries are growing in number in Ethiopia, but there is a dearth of published studies on the prevalence of neck pain. Therefore, this study was aimed to assess the prevalence and associated factors of neck pain among sewing machine operators of garment factories in Mekelle city. Method An institutional-based cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…The position of the garment sewing operators, with their head bowed while sewing, results in neck and lower neck pain. The positioning of the head, which is not in the straight line of the spine, prompts neck pain [8], and increasing the endurance of the neck and shoulder muscles can prevent neck pain [40]. In addition, the prolonged sitting position of a garment-sewing operator promotes complaints of pain in the neck, lower back, and knee [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The position of the garment sewing operators, with their head bowed while sewing, results in neck and lower neck pain. The positioning of the head, which is not in the straight line of the spine, prompts neck pain [8], and increasing the endurance of the neck and shoulder muscles can prevent neck pain [40]. In addition, the prolonged sitting position of a garment-sewing operator promotes complaints of pain in the neck, lower back, and knee [9].…”
Section: Discussionmentioning
confidence: 99%
“…The duration and frequency of program interventions from the study of Marangoni et al [31], with stretching once every six minutes, lasting 10 to 15 s, every day for 15-17 days, can reduce MSDs pain in office workers without changing the work layout, which is considered to disturb the concentration of workers due to the interrupted work time. In this study, the combination of stretching and BG + TfH movements for 5 min in two sessions three times a week, carried out at the side of the desk, did not interfere with work, refreshed workers from monotonous work [6][7][8], and reduced musculoskeletal complaints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the articles show that the highest percentages of the presence of symptoms of musculoskeletal disorders are found in Africa and Asia, where there are maximum percentages of 80% and an average 55% presence of these symptoms in workers in the sector [14]. As such, it was found that the workers who have the greatest impact in the manufacturing industry are female when they are given jobs with high muscular impact, which is why the number of women in the area is small [15].…”
Section: Literature Review a Musculoskeletal Disorders In The Textile...mentioning
confidence: 99%
“…For example, it has been estimated that between 7% and 74% of surgeons suffer from neck-related pain as a result of their job (Alhusuny et al, 2019). In the textile and garment industry, the 12-month prevalence of neck disorders was estimated to be between 42.3% and 46.3%, with males being at higher risk than females (Tafese et al, 2018, Biadgo et al, 2020. Furthermore, epidemiological studies from other occupations such as construction and sedentary computer usage (Tsauo et al, 2007) have reported work-related neck problems at prevalence rates of 38% and 25%, respectively.…”
Section: Introductionmentioning
confidence: 99%